Modulation of host signaling in the inflammatory response by enteropathogenic Escherichia coli virulence proteins - Zhuang, Xiaonan (Cell Mol Immunol, 2017)
To successfully infect host cells and evade the host immune response, a type III secretion system (T3SS) is commonly used by enteric bacterial pathogens such as enteropathogenic Escherichia coli (EPEC). Recent findings have revealed that various effectors are injected into host cells through the T3SS and exert an inhibitory effect on inflammatory signaling pathways, subverting the immune responses to these pathogens. Here we review recent studies aimed at addressing the modulation of several important inflammatory signaling pathways modulated by EPEC effector proteins, such as the nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathways, which provides insight into the unfinished work in this unexplored field and helps to identify novel positions in inflammatory signaling networks for EPEC effectors.